2020
DOI: 10.1021/acs.analchem.0c01844
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Digestion Simulator Reveals pH-Dependent Aggregation in the Gastrointestinal Tract

Abstract: Determining the physicochemical properties of ingested nanoparticles within the gastrointestinal tract (GIT) is critical for evaluating the impact of environmental exposure and potential for nanoparticle drug delivery. However, it is challenging to predict nanoparticle physicochemical properties at the point of intestinal absorption due to the changing chemical environments within the GIT. Herein, a dynamic nanoparticle digestion simulator (NDS) was constructed to examine nanoparticle evolution due to changing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Electrostatically charged polymers, such as polyvinylpyrrolidone (PVP), are frequently used to modify the surface of AgNPs by enhancing the repulsive force between neighboring particles to ensure colloidal stability . However, the repulsive force may be weakened by the salinity and pH of digestive juices, causing AgNPs to aggregate. Representatively, chloride in the gastric fluid is a key element promoting the aggregation of AgNPs in the stomach. The reaction between Cl – and Ag + leached from AgNPs leads to the formation of AgCl in proximity to particles, thereby reducing the repulsive force of the particles and increasing the aggregation rate. , By contrast, the effect of food components, such as oil, starch, and protein, on the aggregation and disaggregation of AgNPs appears to be more convoluted .…”
Section: Transformation Of Agnps Following Oral Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…Electrostatically charged polymers, such as polyvinylpyrrolidone (PVP), are frequently used to modify the surface of AgNPs by enhancing the repulsive force between neighboring particles to ensure colloidal stability . However, the repulsive force may be weakened by the salinity and pH of digestive juices, causing AgNPs to aggregate. Representatively, chloride in the gastric fluid is a key element promoting the aggregation of AgNPs in the stomach. The reaction between Cl – and Ag + leached from AgNPs leads to the formation of AgCl in proximity to particles, thereby reducing the repulsive force of the particles and increasing the aggregation rate. , By contrast, the effect of food components, such as oil, starch, and protein, on the aggregation and disaggregation of AgNPs appears to be more convoluted .…”
Section: Transformation Of Agnps Following Oral Exposurementioning
confidence: 99%
“…It has been demonstrated that AgNPs have a high stability in authentic saliva, most likely as a result of the adsorption of enzymes or other biomolecules on the NP surface, which inhibits aggregation . Instead, AgNPs were seen to first aggregate in the gastric phase of the simulated gastrointestinal digestion and then disaggregate back into well-dispersed particles in the intestinal phase; however, it is unknown why this took place. , …”
Section: Transformation Of Agnps Following Oral Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…[ 3,9,11 ] In order to investigate the gastrointestinal fate of AgNPs, plenty of studies have examined the transformation of AgNPs in artificial GIT fluids through simulating the digestion process from the mouth to the intestine. [ 12–18 ] These in vitro approaches provide an important insight into what AgNPs experience in the GIT before intestinal absorption or excretion from the body, but using simulated digestion models cannot reproduce the complex and dynamic interplay between AgNPs, microenvironment matrices, and cells in the GIT.…”
Section: Introductionmentioning
confidence: 99%
“…This interaction may dramatically modify NBMs’ properties. For instance, the exposure may lead to dissolution [ 42 ], aggregation/agglomeration [ 43 ], and formation of bio-molecular corona [ 44 ] that may change over time. Monitoring such biotransformations is crucial to understand the NBMs biological fate in the gut environment and the impact on their toxicity [ 19 , 45 ].…”
Section: Introductionmentioning
confidence: 99%